Pengukuran erosi pada pertanaman kentang dan jagung padabeberapa kemiringan di desa Guru SingaKabupaten Karo dengan metode USLE - Ananda P Harahap; Hardy Guchi; Jamilah (Talenta Publisher, 2018)
The type of plant and selection of conservation techniques greatly influence the extent of erosion. The aim of this study was to measure the value of the erosion in the field of potato and corn with the slopes by using USLE method (Universal Soil Loss Equation). This study had been implemented in the fields of potato and corn with a slope 0-3, 3-8%,8-15%, 15-25% and 25-45% in Guru Singa village, Berastagi sub-district, Karo district started on April until October 2016. Soil analysis was carried out in Research Laboratories and Technological Faculty of Agriculture, Universitas Sumatera Utara. The result showed that the amount of erosion occurred in the potato field. The field planted by contour direction in slope 0 – 3 % was 4,55 ton ha-1 yr-1 with the low level of erosion hazard. The highest level of erosion hazard in slope 8 – 15 % was 112,57ton ha-1 yr-1. The highest level of erosion hazard in slope 15 – 25 % was 160,97ton ha-1 yr-1. Based on data from the cornfield planted by cutting on contour, the amount of erosion in slope 3 – 8 % was 15,61ton ha-1 yr-1with the middle level of erosion hazard. The highest level of erosion hazard in slope 25 – 45% was 106,08ton ha-1 yr-1. It is required to do the changing of land conservation in order to minimize the risk of erosion or at least equal to the soil erosion tolerated.